The Role of Profitability in Mediating the Influence of Company Size and Leverage on the Value of Manufacturing Companies Listed on the Indonesia Stock Exchange in 2020-2023 - Dewa Ayu Manik Candrapuspa; Ni Made Wahyuni; Ida Ayu Surasmi; Ida Bagus Udayana Putra; I Made Suniastha Amerta; Ni Nengah Seri Ekayani (Jurnal Ekonomi dan Bisnis Jagaditha, 2025)
Bank Indonesia (BI) saw that the manufacturing sector's success in 2023 slowed the rise in company value, as shown by the changing business value. If the growth comes with a high rate of return on investment for shareholders, it will change how many investors or shareholders are worth. There are several ways to figure out how much a business is worth. Before investing, people look at a number of factors that will help them figure out how much a company is worth. This research examines how profitability influences Indonesia Stock Exchange-listed manufacturing businesses' value between 2020 and 2023. It will examine debt and firm size effects on value. Study participants are manufacturers that went public on the Indonesia Stock Exchange between 2020 and 2023. Over four years, 52 firms provided 208 observational data points. The data was collected from public and private archives, which contain papers, documentation, and historical reports. Researchers employ inferential path analysis to solve the question. The research found that company size significantly reduces profitability. Relatively little leverage affects corporate profitability. Size doesn't affect firm worth as much. Leverage boosts corporate value significantly. Profitability has a positive and significant effect on company value. Profitability is able to mediate the effect of company size on company value. Profitability is not able to mediate the effect of leverage on company value.